Structures of sulfide melt crystallization as an indication of metamorphism of the ores in the Oleninskoe gold deposit - Kalinin, A. A.; Savchenko, Ye. E. (2020)
Multiphase fine aggregates of galena, pyrrhotite, freibergite, pyrargyrite, diaphorite, fizelyite, uchucchacuaite, ullmanite, and some other minerals are found in the ores of the Oleninskoe gold deposit in the Kolmozero-Voronya greenstone belt (Kola Peninsula, Russia). The aggregates are considered to be the product of crystallization of sulfide melt formed of the minerals of low-melting-point chalcophile elements (Zn, Ag, Cd, Tl, Pb, As, Sb, Bi, Se, Te, etc.) during heating to the temperature above 500 °C. This origin of the aggregates is affirmed by: 1) multiphase composition (up to 6 minerals) of the aggregates; 2) absence of signs of replacing early minerals by the late ones; 3) essential presence in the aggregates of the minerals of chalcophile elements Ag, Pb, Sb, i. e. elements with a low melting point of their compounds; 4) roundish droplet form of inclusions of minor minerals in the main sulfide, and 5) aggregates' position at the boundary sulfide – quartz or in fractures in vein minerals. Partial melting and crystallization of sulfide melts took place during Paleoproterozoic metamorphic event, when the Neoarchean sulfide-bearing rocks were mid-amphibolite metamorphosed under the temperature > 500 °C. Signs of the Paleoproterozoic metamorphism are found in the ores of the neighboring Cu-Mo porphyry Pellapahk deposit as well. В рудах месторождения золота Оленинское (северо-западная часть зеленокаменного пояса Колмозеро-Воронья, Кольский п-ов, Россия) в краевой части зерен галенита, пирротина, фрейбергита отмечены тонкие полиминеральные срастания, в состав которых кроме перечисленных сульфидов входят пираргирит, диафорит, физелиит, учукчакуаит, ульманит и некоторые другие минералы. Эти срастания рассматриваются нами как результат кристаллизации сульфидного расплава, получившегося при нагреве до температуры свыше 500 °C входящих в состав руды минералов халькофильных элементов, имеющих низкую температуру плавления (Zn, Ag, Cd, Tl, Pb, As, Sb, Bi, Se, Te и некоторые другие). О таком происхождении ...